Exploring the link between dry eye and migraine: From eye to brain - Baksh, Brandon S.; Garcia, Julia Costa [UNESP]; Galor, Anat (Taylor & Francis, 2021)
Dry eye and migraine are common diseases with large societal and economic burdens that have recently been associated in the literature. This review outlines the link between dry eye and migraine, which may have implications for reducing their respective burdens. We highlight possible shared pathophysiology, including peripheral and central sensitization, as the potential link between dry eye and migraine. Finally, therapies targeting similar pathophysiological mechanisms between dry eye and migraine are discussed.
Keywords: Brain; Dry eye; Migraine; Sensitization